2013
DOI: 10.1111/ajt.12230
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus IL-10 Gene Therapy Down-Regulates IL-17 and Attenuates Mouse Orthotopic Lung Allograft Rejection

Abstract: contributed equally to this work.The purpose of the study was to examine the effect of lentivirus-mediated IL-10 gene therapy to target lung allograft rejection in a mouse orthotopic left lung transplantation model. IL-10 may regulate posttransplant immunity mediated by IL-17. Lentivirus-mediated trans-airway luciferase gene transfer to the donor lung resulted in persistent luciferase activity up to 6 months posttransplant in the isograft (B6 to B6); luciferase activity decreased in minor-mismatched allograft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 40 publications
2
23
2
Order By: Relevance
“…21,22,25,[34][35][36][37][38] We have found that fibrosis diminishes over time with surgical experience, and currently we observe minimal fibrosis in allografts not subjected to IRI, in contrast to our earlier data. Allograft fibrosis in the B10→B6 LT model is highly variable among different surgeons and research groups, whereas AR is mild but reproducible.…”
Section: Cold and Warm Ischemic Preservation Augment Allograft Fibrcontrasting
confidence: 92%
“…21,22,25,[34][35][36][37][38] We have found that fibrosis diminishes over time with surgical experience, and currently we observe minimal fibrosis in allografts not subjected to IRI, in contrast to our earlier data. Allograft fibrosis in the B10→B6 LT model is highly variable among different surgeons and research groups, whereas AR is mild but reproducible.…”
Section: Cold and Warm Ischemic Preservation Augment Allograft Fibrcontrasting
confidence: 92%
“…The previous study with this model found a similar incidence of OB, also using C57Bl/6N mice from Harlan Labs (7). However, a recent study did not find evidence of OB using C57Bl/10 lung transplanted to C57Bl/6J mice from Jackson labs (30). We also found the TCRδ −/− mice from Jackson and TCRδ +/− mice, mixed C57Bl/6N and C57Bl/6J background, had a decreased incidence of OB at 25%, although we still found similar pathology to the previous study (7).…”
Section: Discussionmentioning
confidence: 99%
“…They also might reasonably be the focus of possible new drugs or therapeutic approaches, such as the use of IL-10 or other anti-inflammatory biologic agents. Nevertheless, recent studies in patients with other forms of inflammatory liver diseases have not shown benefit of anti-TNF agents [44-47] or IL-10 [48-50], and the use of any of these agents would likely increase the risk of infections. Thus, they should be used in acute DILI only in the context of carefully designed clinical trials.…”
Section: Discussionmentioning
confidence: 99%